2019
DOI: 10.5010/jpb.2019.46.1.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen sources and 2, 4-D treatment on indirect regeneration of ginger (Zingiber officinale Rosc.) using leaf base explants

Abstract: Ginger is an important monocotyledonous plant belonging to the family Zingiberaceae. The objective of this study was to investigate the regeneration potential of ginger using leaf base explants. Auxins such as 2, 4-D and NAA in combination with BA were used for initiation of callus. Different combinations of both ammonium (NH 4+) and nitrate (NO 3-) were also studied for efficient callus production. High frequency of white friable calli was observed on modified Murashige and Skoog (MS) medium supplemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In addition, a developed root system is the crucial step in plant vegetative propagation, which ensures a high survival rate of micropropagated plantlets during the acclimatization stage [ 25 ]. In vitro root induction of ginger is enhanced by auxins supplementation in the culture medium [ 26 , 27 ]. Different types and concentrations of auxin varyingly affected in vitro root induction in different Zingiberaceae species [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a developed root system is the crucial step in plant vegetative propagation, which ensures a high survival rate of micropropagated plantlets during the acclimatization stage [ 25 ]. In vitro root induction of ginger is enhanced by auxins supplementation in the culture medium [ 26 , 27 ]. Different types and concentrations of auxin varyingly affected in vitro root induction in different Zingiberaceae species [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro root induction of ginger is enhanced by auxins supplementation in the culture medium [ 26 , 27 ]. Different types and concentrations of auxin varyingly affected in vitro root induction in different Zingiberaceae species [ 27 , 28 ]. Determining the optimum type and concentration of auxin can significantly enhance the in vitro root induction of ginger and, subsequently, facilitates acclimatization and successful establishment of the in vitro-raised plantlets in the field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro root induction in ginger is further enhanced by supplementing the culture medium with auxins (Abbas et al 2011;Mehaboob et al 2019). Different types and concentrations of auxins have varying effects on in-vitro root induction in different Zingiberaceae species (Mehaboob et al 2019;Jualang et al 2015). Determining the optimum type and concentration of auxin can signi cantly enhance the in-vitro root induction of ginger and facilitate the acclimatization and successful establishment of the in-vitro plantlets in eld conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Mohamed et al (2011) found that shootlets became highly rooted when half strength B5 medium was supplemented with 1.0 mg/L NAA. In-vitro root induction in ginger is further enhanced by supplementing the culture medium with auxins (Abbas et al 2011;Mehaboob et al 2019). Different types and concentrations of auxins have varying effects on in-vitro root induction in different Zingiberaceae species (Mehaboob et al 2019;Jualang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…found that shootlets became highly rooted when half strength B5 medium was supplemented with 1.0 mg/L NAA. In-vitro root induction in ginger is further enhanced by supplementing the culture medium with different nutrients(Abbas et al 2011;Mehaboob et al 2019). Determining the optimum type and concentration of nutrition can signi cantly enhance the in-vitro root induction of ginger and facilitate the acclimatization and successful establishment of the in-vitro plantlets in eld conditions(Mehaboob et al 2019;Jualang et al 2015).…”
mentioning
confidence: 99%